Flexibility of human cytochrome P450 enzymes: molecular dynamics and spectroscopy reveal important function-related variations - Hendrychová, Tereza; Anzenbacherová, Eva; Hudeček, Jiří; Skopalík, Josef; Lange, Reinhard; Hildebrandt, Peter; Otyepka, Michal; Anzenbacher, Pavel (Biochimica et biophysica acta, 2011)
To gain more complete insight into flexibility and malleability of five forms of human liver cytochrome P450 enzymes, which play major roles in drug metabolism (CYPs 1A2, 2A6, 2C9, 2D6 and 3A4), we employed UV/VIS and resonance Raman spectroscopy in combination with all-atomic molecular dynamics simulations under normal and high pressure conditions (300 MPa). In general, the high pressure reduces the flexibility of CYPs, which become more dense and compact as their radii of gyration and temperature B-factors diminish. The flexibility of CYPs spans the regions, which are localized in solvent exposed loops. A considerable degree of flexibility is also observed at amino-acids making the pw2 and solvent channels, which are suggested to serve for substrate access and/or product release. The number of water molecules as well as the number of protein backbone atoms of the active site in close proximity of heme cofactor generally increases under high pressure. This finding provides new insights regarding the interpretation of pressure-related Soret band red shifts. Presented results also point towards considerable differences between the CYP forms studied: CYP2A6 and CYP1A2 have the least malleable active sites while those of CYP2D6, CYP2C9 and CYP3A4 have considerably greater degrees of flexibility or malleability. In addition, the number of water molecules in the active site cavity of CYP3A4 anomalously decreases under high pressure due to opening of the active site. These results correlate with the known substrate promiscuity of the respective CYP forms, with CYP3A4 displaying the highest substrate promiscuity, corresponding to the most open and malleable active site, whereas CYP1A2 and CYP2A6 show a high substrate-specificity and have a small and rigid active sites.
Keywords: cytochrom P-450 CYP3A; Cytochrome P-450 CYP1A2; izoenzymy; simulace molekulární dynamiky; hem; Hydrostatic Pressure; Protein Structure, Tertiary; terciární struktura proteinů; Spectrum Analysis, Raman; Ramanova spektroskopie; Molecular Dynamics Simulation; molekulární modely; Models, Molecular; cytochrom P-450 CYP1A2; substrátová specifita; systém (enzymů) cytochromů P-450; lidé; játra; aromatické hydroxylasy; konformace proteinů; Cytochrome P-450 Enzyme System; Catalytic Domain; Cytochrome P-450 CYP3A; Aryl Hydrocarbon Hydroxylases; Humans; hydrostatický tlak; Substrate Specificity; Isoenzymes; cytochrom P-450 CYP2D6; spektrofotometrie; Spectrophotometry; Protein Conformation; Cytochrome P-450 CYP2D6; Heme; Liver; katalytická doména